Behavioural evidence for separate mechanisms of audiovisual temporal binding as a function of leading sensory modality. (8th April 2016) - Cecere, Roberto; Gross, Joachim; Thut, Gregor
Abstract: The ability to integrate auditory and visual information is critical for effective perception and interaction with the environment, and is thought to be abnormal in some clinical populations. Several studies have investigated the time window over which audiovisual events are integrated, also called the temporal binding window, and revealed asymmetries depending on the order of audiovisual input (i.e. the leading sense). When judging audiovisual simultaneity, the binding window appears narrower and non‐malleable for auditory‐leading stimulus pairs and wider and trainable for visual‐leading pairs. Here we specifically examined the level of independence of binding mechanisms when auditory‐before‐visual vs. visual‐before‐auditory input is bound. Three groups of healthy participants practiced audiovisual simultaneity detection with feedback, selectively training on auditory‐leading stimulus pairs (group 1), visual‐leading stimulus pairs (group 2) or both (group 3). Subsequently, we tested for learning transfer (crossover) from trained stimulus pairs to non‐trained pairs with opposite audiovisual input. Our data confirmed the known asymmetry in size and trainability for auditory–visual vs. visual–auditory binding windows. More importantly, practicing one type of audiovisual integration (e.g. auditory–visual) did not affect the other type (e.g. visual–auditory), even if trainable by within‐condition practice. Together, these results provide crucial evidence that audiovisual temporal binding for auditory‐leading vs. visual‐leading stimulus pairs are independent, possibly tapping into different circuits for audiovisual integration due to engagement of different multisensory sampling mechanisms depending on leading sense. Our results have implications for informing the study of multisensory interactions in healthy participants and clinical populations with dysfunctional multisensory integration. Abstract : We tested whether temporal binding of auditory‐visual (AV) vs. visual‐auditory (VA) stimulus pairs rely on a single or dual mechanism. Three groups of healthy participants performed a simultaneity judgment task with feedback including AV + VA pairs, VA pairs only or AV pairs only. Selective training with one stimulus pair (e.g. AV) had no effect on non‐trained pairs (e.g. VA). The absence of cross‐over suggests separate temporal binding mechanisms for AV and VA according to the leading sense.